ORAL ASSESSMENTS AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Sorohiti, Maryam (Journal of Foreign Language Teaching and Learning, 2016)
Various types of oral assessments such as interviews, presentations and group discussions have commonly been applied at English Education Department of Universitas Muhammadiyah Yogyakarta (EED UMY) to measure students? speaking ability. This research aims to identify both advantages and disadvantages found in the oral assessments applied at EED UMY based on students? perspec- tives. The data were collected using in-depth interviews to six EED UMY students who had taken speaking classes for two semesters. They were interviewed to explore their perception on the advan- tages and disadvantages of the oral assessments they had taken. The findings of this research show that the participants perceived that the oral assessments motivated the students to speak, provided direct feedback, improved students? speaking ability, developed students? communication skills, increased students? self-confidence, and enabled students to share ideas. On the other hand, in addition to insufficient time allocation, the participants also revealed that increased nervousness frequently occurred during oral assessments.